Information spillover and corporate policies: The case of listed options - BERNILE, Gennaro (Institutional Knowledge at Singapore Management University, 2025)
Information production associated with derivatives markets is not a sideshow; rather, it has significantly positive spillover effects on an array of corporate decisions of underlying firms. Using a regression-discontinuity design based on exogenous variation in options availability as an instrument for changes in the information environment, we show that options introductions have causal effects on corporate policies on both sides of the balance sheet. Through improved information efficiency, options availability reduces the need for debt and payout, increases efficient investment, and yields superior innovation. We conduct two independent experiments demonstrating that our instrument s impact is not derived from alternative channels.